Pengaruh Profitabilitas pada Nilai Perusahaan dengan Corporate Social Responsibility Sebagai Variabel Intervening - Wulandewi, A. A. Ayu Tisna; Wirawati, Ni Gusti Putu (E-Jurnal Akuntansi; Vol 22 No 2 (2018)DO - 10.24843/EJA.2018.v22.i02.p27, 2018)
This study aims to obtain empirical evidence on the influence of profitability on corporate value with corporate social responsibility (CSR) as intervening variable. This research is conducted on mining companies listed on Indonesia Stock Exchange 2014- 2016. Sample determination method used is to use purposive sampling technique. The number of companies that meet the criteria is 14 companies with the number of 42 observations. Data collection was done by non participant observation method. Technique Analysis of data used is Path Analysis (Path Analysis). The result of testing in this study shows that profitability variables have a positive effect on firm value. While the CSR variable has no effect on firm value. Profitability variables have a positive effect on CSR disclosure. In this research, CSR's role is not found to mediate the effect of profitability on firm value. Keywords: Profitability, corporate social responsibility, corporate value